Multiple benign metastasizing leiomyoma in the abdominal wall: a case report and literature review - Hu, Jiaqi; Tian, Shuyuan; Pan, Qing; Yu, Yonghong (Frontiers in Oncology, 2024)
Benign metastasizing leiomyoma (BML) is a rare disease that results from metastasis of uterine leiomyoma to distant sites with benign pathologic features. The lung is the most common metastatic site for BML. This report describes the case of a 49-year-old woman who presented with a mass in the abdominal wall with a surgical history of uterine myomectomy. Ultrasound and Magnetic resonance imaging (MRI) revealed multiple mass lesions. The histopathology of the mass specimen indicated BML. The imaging and clinical features of BML are discussed based on the characteristics of this case and related literature reports.